1993
DOI: 10.1002/chin.199334068
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Reaction Potentiality of N‐Aryldichloromaleimides in Diene Reactions with Cyclopentadiene and 1,3‐Cyclohexadiene.

Abstract: 1993 cycloaddition reactions cycloaddition reactions O 0070 34 -068 Reaction Potentiality of N-Aryldichloromaleimides in Diene Reactions with Cyclopentadiene and 1,3-Cyclohexadiene. -Kinetic parameters of cycloaddition reaction of a number of N-aryldichloromaleimides such as (I) with cyclopentadiene and cyclohexadiene are investigated. -(NAGIEV, YA. M.; SAKUILOVA, YA. D.; BAGIROV, SH. T.; SHNULIN, A. N.; ADIGEZALOV, V. A.; NASIBOV, SH. S.; PASHAEV, B. K.; SHAKHTAKHTINSKII, T. N.; Zh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A series of calculations (vide infra) suggested that N -aryl group substitution would have a measurable impact on the relative rates of the intramolecular Diels–Alder reactions. There is limited literature on the effect of aryl substitution of N -arylanilides on Diels–Alder kinetics, even when embedded in the common N -phenylmaleimide dienophile . We thought this matter of general interest due to the relative distance between the electronically differentiated aryl group and the reactive dienophile.…”
Section: Resultsmentioning
confidence: 99%
“…A series of calculations (vide infra) suggested that N -aryl group substitution would have a measurable impact on the relative rates of the intramolecular Diels–Alder reactions. There is limited literature on the effect of aryl substitution of N -arylanilides on Diels–Alder kinetics, even when embedded in the common N -phenylmaleimide dienophile . We thought this matter of general interest due to the relative distance between the electronically differentiated aryl group and the reactive dienophile.…”
Section: Resultsmentioning
confidence: 99%
“…[2,[4][5][6][7][8]. Here we report on the syntheses of new monoand bicyclic compounds proceeding from o-, m-, and p-aminobenzoic acids.…”
mentioning
confidence: 99%
“…The reaction occurred in two steps with initial formation of amido acid A [8] which then underwent cyclization to imide III.…”
mentioning
confidence: 99%
“…We previously studied the Diels-Alder reaction of N-substituted dichloromaleimides with cyclopentadiene [2,[5][6][7], which led to the formation of bicyclic adducts, and examined the structure and properties of the products, as well as some general relations holding in this reaction. In continuation of studies in this line, the present communication reports on the Diels-Alder reaction of N-substituted dichloromaleimides with 1,3-cyclohexadiene.…”
mentioning
confidence: 99%